Del Noce's critique of Maritain and the intellectual origins of left Catholicism - Hoevel, Carlos (Cultura Económica, 2021)
Although Augusto Del Noce recognizes himself as a disciple and admirer of Maritain, in his famous book The Problem of Atheism, he makes a strong criticism of his teacher as a result of the latter's acceptance of certain social and economic theses of Marxism. Attributing the cause of Maritain's position to a central flaw in his view of modern philosophy and history, Del Noce will accuse Maritain of inadvertently introducing into Catholic social thought a perfectist-utopian germ incompatible with Christianity. From this criticism the Italian philosopher will leave clues in his writings about the influences on other Christian thinkers of this Maritainian openness to Marxism. In this sense, Del Noce's thinking is an effective starting point for exploring the intellectual genesis of left-wing Catholicism, both in Europe and in Latin America, in recent decades with influence to this day.